2011
DOI: 10.1007/s10658-011-9879-y
|View full text |Cite
|
Sign up to set email alerts
|

Global incidence of wheat rusts and powdery mildew during 1969–2010 and durability of resistance of winter wheat variety Bezostaya 1

Abstract: Disease incidence and severity was studied for winter wheat variety Bezostaya 1 and susceptible checks based on data from international nurseries from 1969 to 2010 and from 51 countries across major winter wheat production regions totalling 1,047 reports. The frequency of leaf rust and stripe rust occurrence was stable over time with marked increases in severity in 2001-2010 especially in Europe and Central and West Asia. Substantial global reductions in stem rust occurrence were recorded and attributed primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 23 publications
0
77
0
Order By: Relevance
“…Increased infection rates were also reported for stripe rust during the same time periods (Morgounov et al 2012). The severity of this rust species increased from 14% in 1969-1981 to 17% in 1988-2000 and 26% in 2001-2010.…”
Section: Assessment Of the Origin Of Lr34 Resistance Alleles In Turkimentioning
confidence: 56%
See 3 more Smart Citations
“…Increased infection rates were also reported for stripe rust during the same time periods (Morgounov et al 2012). The severity of this rust species increased from 14% in 1969-1981 to 17% in 1988-2000 and 26% in 2001-2010.…”
Section: Assessment Of the Origin Of Lr34 Resistance Alleles In Turkimentioning
confidence: 56%
“…Contrary to leaf and stripe rust, Morgounov et al (2012) observed a reduction of 38% in the occurrence of stem rust from 1969 to 1981, and of 7% from 2001 to 2010. Despite this decrease in disease incidence, in Bezostaya 1 disease severity increased from 28% in 1969-1981 to 42% in 2001-2010.…”
Section: Assessment Of the Origin Of Lr34 Resistance Alleles In Turkimentioning
confidence: 60%
See 2 more Smart Citations
“…Powdery mildew (Pm), caused by Blumeria graminis f. sp. tritici (Bgt), is a severe and globally significant disease of common wheat, with an occurrence of about 54 % in crops worldwide during 2001-2010(Morgounov et al 2012. Yield losses caused by the disease range from 13 to 34 %, but if the disease is severe losses can exceed 50 % (Griffey et al 1993).…”
Section: Introductionmentioning
confidence: 99%